Teknik agroforestri di areal hutan kemasyarakatan desa Pejarakan, kecamatan Gerokgak, kabupaten Buleleng, provinsi Bali - I Putu Gede Ardhana (Institut Pertanian Bogor, 2011)
Since 2003 year the technic of agroforestry with alley cropping systems has been implemented at the forest areas in Pejarakan Village, District Gerokgak, Regency of Buleleng Province Bali. These activities are expected to support the progress of welfare for farmers, eventhough they have been neglected to preserve forest around village. After the research it was cleared that the result of activities didn't fulfilled to its expectation. The analysis about the compositions and structures of vegetations in this research shows that the dominant type of species which are mainly cultivated have character of Importance Value Index, the balance of species among Diversity Index are still low at all of the communal forest areas and even at the these slope sides. The composition and the structure of species were still few, and the vegetation it self was disturbed by people, in order to illegal longings, cuttings top branches or twigs often occur, and these activities obstacle growth of trees in communal forest areas. It is concluded that the technic of agroforestry at the communal forest areas has few compositions of species and structure of vegetations, so the diversity of species become very poor and not stable either for plants in forestry or for agricultural crops. The researcher could not determine that what species of vegetations superior at this area. So it necessary to enough time for intensive observations and research at this communal forest areas.